Ongoing symptoms after eradication of Helicobacter pylori: Psychiatric disorders may accompany! - Hakan Ümit ÜNAL; Ebru Akın; İsmail AYDIN and Murat Korkmaz and Sevgi ÖZEL and Haldun Selçuk and Uğur Yılmaz (Turkish Journal of Gastroenterology, 2019)
-